Folklore in EFL: The Local Wisdom Implementation of Indonesian Curriculum - Prasetyo, Ade (University of Muhammadiyah Prof. DR. HAMKA, 2016)
This article attempts to present an independent argument with regard to the importance of using local folklore in EFL. As it is clearly mentioned in the 2013 curriculum (K-13) and the following curriculum, National Curriculum, applying local wisdom is a cardinal aspect to be involved in the teaching-learning processes. Applying local wisdom is also believed to be one of strives to conserve and appreciate Indonesian cultural heritage and some cultural heritage that may not have been exposed before. Yet, it seems that using local folklore in EFL still lacks serious attention. In general, providing folklore is not only beneficial to keep the cultural heritage but also advantageous to, among others, help EFL students study English, help them gain cultural acquisition, and provide them with positive values for their character building. In short, engaging local contents has been officially stated in the K-13 and National Curriculum; however, its implementation is likely to be unpopular.